Care for Patients with Stroke During the COVID-19 Pandemic: Physical Therapy and Rehabilitation Suggestions for Preventing Secondary Stroke (2020)
Infection with the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes the development of the novel 2019 coronavirus disease (COVID-19) and associated clinical symptoms, which typically presents as an upper respiratory syndrome such as pneumonia. Growing evidence indicates an increased prevalence of neurological involvement (e.g., in the form of stroke) during virus infection. COVID-19 has been suggested to be more than a lung infection because it affects the vasculature of the lungs and other organs and increases the risk of thrombosis. Patients with stroke are vulnerable to secondary events as a result not only of their poor vascular condition but also of their lack of access to rehabilitation resources. Herein, we review current knowledge regarding the pathophysiology of COVID-19, its possible association with neurological involvement, and current drug therapies. Suggestions are also offered regarding the potential for current neurorehabilitation therapies to be taught and practiced at home.